2018
DOI: 10.1002/acp.3388
|View full text |Cite
|
Sign up to set email alerts
|

Interpreters in law enforcement contexts: Practices and experiences according to investigators

Abstract: SummaryInterpreters play an important role in the criminal justice system, yet little is known about the way interpreters are used. This survey of U.S. law enforcement (N = 299) assessed practices and perceptions regarding interpreter use during interviews with nonnative English speakers. Investigators reported using colleagues more often than professional interpreters, using interpreters more often with suspects and in certain crimes (e.g., domestic violence), and that interpreters are usually at least partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…After contacting over 2,000 police and sheriff’s departments, the final sample included a diverse array of United States law enforcement professionals ranking from chief of police to polygraph examiner ( N = 388; see Table 1). This recruitment yield is similar to that in previous related studies (e.g., Rivard and Schreiber Compo, 2017; Shaffer and Evans, 2018). A third of the sample reported having been at their current rank for 1–3 years, while 22% reported having been at their current rank for 4–7 years, 10% reported having been at their current rank for 8–10 years and 25% reported to have been at their current rank for over 10 years.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…After contacting over 2,000 police and sheriff’s departments, the final sample included a diverse array of United States law enforcement professionals ranking from chief of police to polygraph examiner ( N = 388; see Table 1). This recruitment yield is similar to that in previous related studies (e.g., Rivard and Schreiber Compo, 2017; Shaffer and Evans, 2018). A third of the sample reported having been at their current rank for 1–3 years, while 22% reported having been at their current rank for 4–7 years, 10% reported having been at their current rank for 8–10 years and 25% reported to have been at their current rank for over 10 years.…”
Section: Methodssupporting
confidence: 90%
“…However, it can be argued that examining the perceptions, beliefs and self-reported practices of law enforcement is equally important. Further, although the response rate is similar to that of related research (e.g., Rivard and Schreiber Compo, 2017;Shaffer and Evans, 2018), the response rate was low, thus limiting how representative the sample is of the population. We also did not collect data regarding the participants' demographics (e.g., age, gender, ethnicity) or department size to increase potential participants' comfort with staying anonymous, thus increasing real-world investigators' willingness to participate.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…Second, surveys of investigative interviewing practitioners have been conducted by teams of psychologists in different countries and jurisdictions, some of which have focused on interpreted police interviews (e.g., Shaffer & Evans, 2018 in the USA; Wakefield et al, 2014 in Australia). Although some research teams administered identical surveys in different jurisdictions (e.g., Miller, Redlich, & Kelly, 2018;Redlich, Kelly, & Miller, 2014;Sivasubramaniam & Goodman-Delahunty, 2019), no rigorous jurisdictional comparisons of the outcomes on interpreting have been undertaken.…”
Section: Field Surveys Of Stakeholders In Interpreted Police Interviewsmentioning
confidence: 99%
“…
Criminal justice proceedings are high-stakes settings in which native English speakers have difficulty negotiating the legal process, let alone persons with no or limited English proficiency. Increasingly, law enforcement interviewers are required to rely on interpreters (Mulayim & Lai, 2017;Shaffer & Evans, 2018). However, the mere presence of an interpreter does not guarantee accurate interpreting.
…”
mentioning
confidence: 99%
“…Wilson and Walsh (2019) found that mistrust exists between investigators and interpreters, exemplified in their study through police officers' reluctance either to engage with interpreters in interview planning or (where planning did occur) to discuss their role/s within the interview in a collaborative manner, preferring to focus on each of their individual roles instead. Shaffer and Evans (2018) found, in their survey of US investigators, a preference to use bi-lingual colleagues as interpreters. One source of mistrust appears to be disagreement concerning the specific role of interpreters.…”
Section: Rapport-building and Maintenancementioning
confidence: 99%